Optimasi helm industri ergonomik beserta perancangan dan simulasi molding injeksi - Arif Budi Wicaksono; Abdul Aziz (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
This research purpose to develop an innovative industrial helmet design that can be integrated with face and ear protection using Triz40 method and then analyzes, designs and simulates injection molding innovations. Injection molding in this study uses two plates. Then industrial helmet model was realized using a 3d print with PLA material. In addition, this study aims to see the effect variations number of gates on filling time and quality predictions. The number of gates varied into 3 types, namely 1, 2 and 4 gates. The results obtained optimally use 1 gate with optimal charging time, defects and prediction of quality. The optimum mold unit dimension is 500 x 500 mm with a clamping force of 3986.86 kN.